IMPACT OF NIGHT SHIFTS ON SYMPTOMS OF BURNOUT AND DEPRESSION IN OBSTETRICS AND GYNECOLOGY RESIDENTS (CIPEEX, 2025)
INTRODUCTION: Burnout syndrome is defined as exhaustion resulting from excessive demands on energy, strength, or resources in performing a given activity. Depressive disorder consists of symptoms such as depressed mood, loss of interest/pleasure, and decreased energy, impairing individuals' ability to perform daily activities. Medical residency is an important stage in the training of medical specialists. Although this period provides new knowledge, skills, and competencies, it also requires a heavy workload, responsibilities, demands, and personal obligations. Given this, it is clear that the population of medical residents, especially those in gynecology and obstetrics (GO), is more exposed to factors that contribute to the development of anxiety, depression, and Burnout Syndrome. In addition, it is necessary to know that one of the aggravating factors of the situation is the shift worked, with night shifts being considered the most exhausting. From this perspective, there are still gaps in our knowledge about the night work of OB/GYN residents and its influence and impact on the development of depression and burnout syndrome in these individuals. OBJECTIVE: To analyze the impacts of night shifts on symptoms of burnout and depression in gynecology and obstetrics residents. METHODOLOGY: This is a literature review based on five articles in English, Spanish, and Portuguese published in PubMed, Scielo, and BVS over the last five years, using the following keywords: “Anxiety,” “Burnout,” “Depression,” and “Medical residency.” RESULTS: The literature shows that most of the population studied reported sleep deprivation, less supervision at night, and social isolation during shifts, which causes fatigue and chronic stress, in addition to increasing emotional exhaustion, depersonalization, reduced mood, risk of error during procedures, and impaired well-being (loss of quality of life). Studies also show that, when comparing night and day shifts, greater emotional exhaustion and lower personal fulfillment occur in residents during night shifts, in addition to suggesting that longer shift hours and lack of days off are predictors of burnout syndrome and depression. Associated with this, the duration and frequency of night shifts contribute significantly to the emergence of symptoms of burnout and depression in OB/GYN residents. Therefore, all studies have shown that OB/GYN residents who work night shifts have a high prevalence of burnout and depressive symptoms. CONCLUSION: It is clear that gynecology and obstetrics residents who work night shifts experience high levels of emotional exhaustion and a lower sense of personal fulfillment, which explains the significant prevalence of burnout and depression symptoms in these individuals. Therefore, there is a need to adjust the workload and structure of night shifts, combined with emotional support and mental health programs for residents.
Keywords: “Anxiety.” “Burnout.” “Depression.” “Medical residency.”